Review and Critical Analysis of Privacy-Preserving Infection Tracking and Contact Tracing - Buchanan, William J.; Imran, Muhammad Ali; Ur-Rehman, Masood; Zhang, Lei; Abbasi, Qammer H.; Chrysoulas, Christos; Haynes, David; Pitropakis, Nikolaos; Papadopoulos, Pavlos (Frontiers in Communications and Networks, 2020)
The outbreak of viruses have necessitated contact tracing and infection tracking methods. Despite various efforts, there is currently no standard scheme for the tracing and tracking. Many nations of the world have therefore, developed their own ways where carriers of disease could be tracked and their contacts traced. These are generalized methods developed either in a distributed manner giving citizens control of their identity or in a centralised manner where a health authority gathers data on those who are carriers. This paper outlines some of the most significant approaches that have been established for contact tracing around the world. A comprehensive review on the key enabling methods used to realise the infrastructure around these infection tracking and contact tracing methods is also presented and recommendations are made for the most effective way to develop such a practice.